Preparation method and application of ABS (Acrylonitrile Butadiene Styrene) grafted latex
By controlling the proportion of C16 components in the emulsifier during the emulsifier graft polymerization process, the problem of the decrease in emulsion stability after MMA is solved, the stability of the emulsion polymerization system is improved, and the continuous and stable production and low production of transparent ABS resin are achieved. Haze finished product.
Patent Information
- Application Number
- CN202411774704.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-05
AI Technical Summary
During the emulsion graft polymerization process, the introduction of MMA causes the emulsion stability to decrease, which is prone to a large-scale demulsification phenomenon, affecting the continuous and stable production of transparent ABS resin.
By controlling the proportion of C16 components in the emulsifier used during emulsion graft polymerization, the stability of the emulsion polymerization system is improved, thereby reducing the slag and reducing the haze of the finished resin.
It improves the stability of the emulsion polymerization system, reduces the amount of slag output, reduces the haze of transparent ABS resin, and achieves continuous and stable production of products.
Smart Images

Figure BDA0005171115240000111
Abstract
Description
Technical Field
[0001] The invention relates to the field of ABS resin, and in particular to a preparation method and application of ABS grafted latex. Background Art
[0002] ABS resin is a ternary copolymer of acrylonitrile (A), butadiene (B) and styrene (S).
[0003] Due to the large difference in refractive index between its dispersed phase polybutadiene latex particles and the continuous phase SAN, ABS resin is usually opaque and cannot be used to prepare transparent products.
[0004] To prepare transparent ABS resin, the following two methods are generally used in the prior art:
[0005] 1) Reduce the particle size of the raw material polybutadiene latex, thereby reducing the refraction / scattering of visible light at the two-phase interface and achieving transparency; however, after the particle size of the polybutadiene latex is reduced, the impact performance of the product is significantly reduced, affecting the application of the product. Therefore, this method is rarely used.
[0006] 2) Use copolymerization to increase the refractive index of the dispersed phase or reduce the continuous phase, so that the refractive index of the two phases matches, and eliminates the refraction / scattering on the interface of the two phases to achieve transparency. For example, patent CN101336255A uses MMA / styrene / acrylonitrile copolymerization to reduce the refractive index of the continuous phase to within 0.002 of the dispersed phase, thereby achieving transparent ABS preparation.
[0007] Patent CN104136530B adopts copolymerization of acrylic acid ester monomers to adjust the refractive index difference of dispersed phase polybutadiene latex, polybutadiene latex graft, and continuous phase SAN to <0.005, thereby realizing the preparation of transparent ABS.
[0008] Patent CN114736334A adopts the method of introducing styrene copolymerization into the dispersed phase and introducing acrylic ester monomer copolymerization into the continuous phase to control the difference in refractive index between the two phases, thereby achieving resin transparency.
[0009] The above methods can achieve the preparation of transparent ABS, but in the actual production process, when emulsion graft polymerization is used to prepare polybutadiene latex graft containing MMA as mentioned in patent CN104136530B, the introduction of MMA will greatly reduce its stability during the emulsion polymerization process, and large-scale demulsification is very likely to occur. This phenomenon makes the continuous and stable production of transparent ABS extremely challenging.
[0010] Therefore, it is necessary to further improve the instability of the emulsion after the introduction of MMA into the emulsion grafting polymerization system, so as to achieve continuous and stable production of transparent ABS resin. Summary of the invention
[0011] In order to solve the above technical problems, the present invention provides a method for preparing ABS grafted latex and its application. The method improves the stability of the emulsion polymerization system by controlling the proportion of C16 components in the emulsifier used in the emulsion graft polymerization process, thereby reducing the amount of slag during the reaction and significantly reducing the haze index of the finished resin.
[0012] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0013] An ABS grafted latex comprises polybutadiene latex, a comonomer, an emulsifier and an initiator.
[0014] Preferably, the amount of the comonomer is 50-200% of the dry weight of the polybutadiene latex;
[0015] Preferably, the emulsifier is used in an amount of 0.5-5% of the dry weight of the polybutadiene latex; and / or,
[0016] Preferably, the total amount of the initiator is 0.1-1% of the dry weight of the polybutadiene latex;
[0017] The comonomers include styrene monomers, acrylonitrile monomers, and methacrylate monomers.
[0018] The styrene monomer is selected from one or more of styrene, α-methylstyrene, p-methylstyrene and vinyltoluene;
[0019] The acrylonitrile monomer is one or more selected from acrylonitrile, methacrylonitrile and ethacrylonitrile;
[0020] The methacrylate monomer is selected from one or more of methyl methacrylate, ethyl methacrylate, propyl methacrylate, and 2-ethylhexyl methacrylate;
[0021] The emulsifier is selected from carboxylates with 10 to 20 carbon atoms, preferably one or more of potassium oleate and fatty soap, and the mass proportion of carboxylates with less than 17 carbon atoms in the emulsifier is greater than 20%;
[0022] The initiator is a peroxide, preferably one or more of dicumyl peroxide, cumyl hydroperoxide, and tert-butyl hydroperoxide.
[0023] As a preferred embodiment of the present invention, the comonomer comprises the following raw materials in weight ratio based on the total mass of 100%:
[0024] The styrene monomer is 10-30wt%, the acrylonitrile monomer is 5-20wt%, and the methacrylate monomer is 60-80wt%.
[0025] As a preferred embodiment of the present invention, the particle size of the polybutadiene latex is 260-350 nm, and the solid content is 40-60 wt%.
[0026] The preparation process of the polybutadiene latex is known, for example, it can be prepared by referring to the scheme in patent CN107001515A, which will not be described in detail here.
[0027] As a preferred embodiment of the present invention, a chain transfer agent, a complexing agent, a reducing agent, a co-reducing agent or water is also added into the polymerization reaction.
[0028] As a preferred embodiment of the present invention, the chain transfer agent is one of n-octyl mercaptan, tert-dodecyl mercaptan, and n-dodecyl mercaptan, preferably tert-dodecyl mercaptan; and / or,
[0029] The complexing agent is one or more of trisodium nitrilotriacetate, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium pyrophosphate, sodium hexametaphosphate, preferably sodium pyrophosphate; and / or,
[0030] The auxiliary reducing agent is one or more of sodium dithionite, sodium formaldehyde sulfoxylate, isoascorbic acid, glucose, and lactose, preferably glucose; and / or,
[0031] The reducing agent is one or more of ferrous sulfate, ferrous chloride, and sodium bisulfite, preferably ferrous sulfate.
[0032] The amount of the chain transfer agent is 0.1-1% of the dry weight of the polybutadiene latex; and / or,
[0033] The complexing agent is used in an amount of 0.1-1% of the dry weight of the polybutadiene latex; and / or,
[0034] The reducing agent is used in an amount of 0.001-0.01% of the dry weight of the polybutadiene latex; and / or,
[0035] The amount of the reducing agent is 0.1-1% of the dry weight of the polybutadiene latex; and / or,
[0036] The amount of water used is 50-100% of the dry weight of the polybutadiene latex.
[0037] A method for preparing ABS grafted latex comprises the following steps: mixing polybutadiene latex, comonomer, emulsifier and initiator to polymerize to obtain ABS grafted latex;
[0038] The comonomer can be added in batches or continuously by dropwise addition;
[0039] As a preferred embodiment of the present invention, the total amount of the comonomer is 50-200% of the dry weight of the polybutadiene latex;
[0040] As a preferred embodiment of the present invention, the preparation method comprises:
[0041] 1) Base stage: Add polybutadiene latex, part of the comonomer, part of the initiator, emulsifier and water into the reactor, stir and swell first and then heat to polymerize;
[0042] 2) Continuous dropping stage: the remaining comonomers and initiators are added dropwise to the reactor and the reaction is continued until complete to obtain ABS grafted latex.
[0043] Preferably, in step 1), the polymerization reaction temperature is 40-80°C, preferably 50-70°C;
[0044] Preferably, the amount of the comonomer added in step 1) is 10-50% of the total mass of the comonomer.
[0045] Preferably, the amount of the initiator added in step 1) is 10-50% of the total mass of the initiator. Preferably, in step 2), the polymerization reaction temperature is 40-90°C, preferably 50-80°C;
[0046] Preferably, in step 2), the dropping time of the comonomer and the initiator is 1-5 hours.
[0047] In step 2), the reaction is considered complete when the total conversion of the comonomers is >96%.
[0048] The invention discloses an application of the ABS grafted latex prepared according to the method described above in the preparation of transparent ABS resin.
[0049] A method for preparing a transparent ABS resin comprises the following steps: agglomerating and demulsifying the ABS grafted latex prepared by the method to obtain ABS rubber powder, and then mixing and extruding it with a methacrylate-styrene-acrylonitrile copolymer (MSAN resin) through an extruder to obtain a transparent ABS resin.
[0050] Wherein, MSAN resin refers to methyl methacrylate-styrene-acrylonitrile copolymer with a refractive index of 1.515±0.005, and preferably has a weight average molecular weight of 100,000-140,000.
[0051] The MSAN resin can be prepared by any known method (such as bulk polymerization), or can be directly purchased from commercial products (such as LG Chemical XT500), without any limitation herein.
[0052] The method for coagulation and demulsification of the ABS grafted latex is known to those skilled in the art, and mainly comprises mixing the ABS grafted latex with an inorganic acid or its salt, aging at high temperature, filtering and drying to obtain ABS rubber powder.
[0053] The mass ratio of the ABS rubber powder and the MSAN resin can be (20-30):(70-80), and after being mixed and extruded at 200-220° C., the transparent ABS resin is obtained through cooling and granulation.
[0054] The researchers of the present invention found that when MMA was introduced into the emulsion graft polymerization, there was a significant difference in hydrophilicity between the latex shell resin MSAN and the shell SAN of the general ABS latex (the contact angle difference between the two was >10°). This difference caused the arrangement of the original emulsifier on the shell to change. The MSAN shell emulsifier with better hydrophilicity tended to be arranged in an inverted manner, and the electrostatic repulsion for maintaining the stability of the emulsion was significantly weakened, so it was more prone to large-scale demulsification.
[0055] The present invention adopts an emulsifier with a specific composition, which has a shorter chain length and a smaller attachment area on the shell layer. When the hydrophilicity of the shell layer changes, the electrostatic repulsion caused by lodging does not decrease significantly, thereby improving the stability of MMA during the emulsion graft polymerization reaction, making the process continuity of the ABS graft latex production process better, and significantly reducing the amount of slag in the production process. When further prepared into a transparent ABS resin, the finished product has a lower haze level. DETAILED DESCRIPTION
[0056] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0057] Unless otherwise specified, the raw materials used in the following specific embodiments of the present invention can be obtained through commercial channels. Among them, polybutadiene latex is prepared by referring to the method of Example 1 in patent CN107001515A, and by adjusting the addition amount of 1,3-butadiene and ion exchange water, polybutadiene latex A (particle size 303nm, solid content 56.3%), polybutadiene latex B (particle size 272nm, solid content 55.7%), and polybutadiene latex C (particle size 336nm, solid content 57.1%) are prepared respectively.
[0058] MSAN resin: brand XT500, purchased from LG Chemical.
[0059] Potassium oleate and fatty soap containing carboxylate components with less than 17 carbon atoms accounting for more than 20% can be produced by manufacturers by controlling the types of raw oils and fats, or by adding potassium hydroxide neutralization products such as hexadecanoic acid and tetradecanoic acid purchased from outside to crude oil potassium oleate and fatty soap.
[0060] The main methods used in the following specific embodiments of the present invention are as follows:
[0061] (1) Latex particle size: 1 g of latex was mixed with 100 g of deionized water, and the average particle size was measured using a Malvern Mastersizer laser particle size analyzer according to the dynamic laser scattering method;
[0062] (2) Latex solid content / conversion rate: 2 g of grafted latex was dried at 180°C using a Mettler HC103 moisture meter to obtain the solid content; the conversion rate of the grafting process can be calculated based on the feed formula, or the conversion rate can be calculated by gas chromatography testing of residual comonomers;
[0063] (3) Latex stability: According to GB / T 20623, weigh 400 g of latex and use a high-speed disperser at 2500 r / min to disperse for 0.5 h, then filter with a 100-mesh filter to observe whether the latex is demulsified and has obvious flocculants, and weigh the weight of the residue on the filter;
[0064] (4) Impact performance test: ABS resin slices were used to prepare samples and perform impact performance tests according to the GB / T1043 hard plastic simply supported beam impact test method;
[0065] (5) Transmittance / haze: The resin was sampled according to ASTM D1003 and tested three times using a Hazegard 1 transmittance and haze meter at different areas of the optical plate to obtain the transmittance and haze values.
[0066] In the specific implementation manner of the present invention, each raw material portion is a mass portion.
[0067] [Example 1]
[0068] 177.8 parts of polybutadiene latex A (100 parts by dry weight), 20 parts of comonomers (22 wt% styrene, 8 wt% acrylonitrile, 70 wt% methyl methacrylate), 1.5 parts of fatty soap (the content of carboxylates with less than 17 carbon atoms is adjusted to 27.72% by adding potassium n-decanoate), 0.3 parts of tert-dodecyl mercaptan, 0.1 parts of sodium pyrophosphate, 0.1 parts of glucose, 0.005 parts of ferrous sulfate, 0.04 parts of cumene hydroperoxide, and 100 parts of water are added into a reactor, and the mixture is stirred and mixed thoroughly for swelling for 0.5 h, and then heated to 70° C., and the remaining 40 parts of comonomers (22 wt% styrene, 8 wt% acrylonitrile, 70 wt% methyl methacrylate) and 0.16 parts of cumene hydroperoxide are added dropwise into the reactor at a constant rate within 3 h, and the temperature is raised to 80° C. to continue the reaction. When the total conversion rate of the comonomers is 97.53%, the temperature is lowered to obtain ABS grafted latex.
[0069] [Example 2]
[0070] 175.7 parts of polybutadiene latex B (100 parts by dry weight), 50 parts of comonomers (30 wt% of α-methylstyrene, 10 wt% of acrylonitrile, 60 wt% of MMA), 2 parts of potassium oleate (the content of carboxylates with less than 17 carbon atoms is adjusted to 34.04% by adding potassium laurate), 0.2 parts of tert-dodecyl mercaptan, 0.2 parts of sodium pyrophosphate, 0.2 parts of lactose, 0.003 parts of ferrous sulfate, 0.2 parts of tert-butyl hydroperoxide, and 60 parts of water are added into a reactor, and the mixture is stirred and swollen for 0.5 hours, and then heated to 65° C., and the remaining 50 parts of comonomers (30 wt% of α-methylstyrene, 10 wt% of acrylonitrile, 60 wt% of MMA) and 0.6 parts of tert-butyl hydroperoxide are added dropwise into the reactor at a constant rate within 4 hours, and the temperature is raised to 75° C. to continue the reaction. When the total conversion rate of the comonomers is 96.68%, the temperature is lowered to obtain ABS grafted latex.
[0071] [Example 3]
[0072] 175.7 parts of polybutadiene latex B (100 parts by dry weight), 50 parts of comonomers (15 wt% styrene, 20 wt% methacrylonitrile, 65 wt% MMA), 3 parts of potassium oleate (the content of carboxylates with less than 17 carbon atoms is adjusted to 48.6% by adding potassium tetradecanoate), 0.5 parts of n-octyl mercaptan, 0.5 parts of tetrasodium ethylenediaminetetraacetate, 0.7 parts of sodium formaldehyde sulfoxylate, 0.009 parts of ferrous chloride, 0.1 parts of diisopropylbenzene peroxide, and 80 parts of water are added into a reactor, and the mixture is stirred and swollen for 0.5 h, and then heated to 60° C., and the remaining 100 parts of comonomers (15 wt% styrene, 20 wt% methacrylonitrile, 65 wt% MMA) and 0.3 parts of diisopropylbenzene peroxide are added dropwise into the reactor at a constant rate within 5 h, and the temperature is raised to 70° C. to continue the reaction. When the total conversion rate of the comonomers is 96.11%, the temperature is lowered to obtain ABS grafted latex.
[0073] [Example 4]
[0074] 178.1 parts of polybutadiene latex C (100 parts by dry weight), 10 parts of comonomers (20 wt% styrene, 5 wt% acrylonitrile, 75 wt% ethyl methacrylate), 4 parts of fatty soap (the content of carboxylates with less than 17 carbon atoms is adjusted to 53.9% by adding potassium hexadecanoate), 0.5 parts of n-dodecyl mercaptan, 0.7 parts of sodium hexametaphosphate, 0.2 parts of lactose, 0.005 parts of sodium bisulfite, 0.1 parts of cumene hydroperoxide, and 90 parts of water are added into a reactor, and the mixture is stirred and mixed thoroughly for swelling for 0.5 h, and then heated to 60° C., and the remaining 40 parts of comonomers (20 wt% styrene, 5 wt% acrylonitrile, 75 wt% ethyl methacrylate) and 0.3 parts of cumene hydroperoxide are added dropwise into the reactor at a constant rate within 3 h, and the temperature is raised to 80° C. to continue the reaction. When the total conversion rate of the comonomers is 97.24%, the temperature is lowered to obtain ABS grafted latex.
[0075] [Example 5]
[0076] 178.1 parts of polybutadiene latex C (100 parts by dry weight), 10 parts of comonomers (20 wt% styrene, 5 wt% acrylonitrile, 75 wt% methyl methacrylate), 4 parts of fatty soap (the content of carboxylates with less than 17 carbon atoms is adjusted to 68.6% by adding potassium hexadecanoate), 0.7 parts of tert-dodecyl mercaptan, 0.2 parts of sodium pyrophosphate, 0.3 parts of lactose, 0.002 parts of ferrous sulfate, 0.05 parts of cumene hydroperoxide, and 80 parts of water are added into a reactor, and the mixture is stirred and mixed thoroughly for swelling for 0.5 h, and then heated to 60° C., and the remaining 40 parts of comonomers (20 wt% styrene, 5 wt% acrylonitrile, 75 wt% methyl methacrylate) and 0.25 parts of cumene hydroperoxide are added dropwise into the reactor at a constant rate within 4 h, and the temperature is raised to 80° C. to continue the reaction. When the total conversion rate of the comonomers is 97.65%, the temperature is lowered to obtain ABS grafted latex.
[0077] [Comparative Example 1]
[0078] 177.8 parts of polybutadiene latex A (100 parts by dry weight), 20 parts of comonomers (22 wt% styrene, 8 wt% acrylonitrile, 70 wt% methyl methacrylate), 1.5 parts of fatty soap (the content of carboxylates with less than 17 carbon atoms was 4.88% when tested), 0.3 parts of tert-dodecyl mercaptan, 0.1 parts of sodium pyrophosphate, 0.1 parts of glucose, 0.005 parts of ferrous sulfate, 0.04 parts of cumene hydroperoxide and 100 parts of water were added into a reactor, stirred and mixed thoroughly for swelling for 0.5 h, and then heated to 70° C., the remaining 40 parts of comonomers (22 wt% styrene, 8 wt% acrylonitrile, 70 wt% methyl methacrylate) and 0.16 parts of cumene hydroperoxide were added dropwise into the reactor at a constant rate within 3 h, and the temperature was raised to 80° C. to continue the reaction. When the total conversion rate of the comonomers reached 97.14%, the temperature was lowered to obtain ABS grafted latex.
[0079] [Comparative Example 2]
[0080] 175.7 parts of polybutadiene latex B (100 parts by dry weight), 50 parts of comonomers (22 wt% styrene, 8 wt% acrylonitrile, 70 wt% methyl methacrylate), 2 parts of potassium oleate (the content of carboxylates with less than 17 carbon atoms was tested to be 7.7%), 0.5 parts of tert-dodecyl mercaptan, 0.5 parts of sodium pyrophosphate, 0.5 parts of lactose, 0.002 parts of ferrous sulfate, 0.1 parts of tert-butyl hydroperoxide, and 80 parts of water were added into a reactor, stirred and mixed thoroughly for swelling for 0.5 h, and then heated to 60° C., the remaining 50 parts of comonomers (22 wt% styrene, 8 wt% acrylonitrile, 70 wt% methyl methacrylate) and 0.3 parts of tert-butyl hydroperoxide were added dropwise into the reactor at a constant rate within 4 h, and the temperature was raised to 80° C. to continue the reaction. When the total conversion rate of the comonomers was 96.55%, the temperature was lowered to obtain ABS grafted latex.
[0081] The particle size, solid content, and emulsion stability of the ABS grafted latex prepared in each embodiment and comparative example were tested. The performance test structure is shown in Table 1.
[0082] The ABS grafted latex prepared in the embodiment of the present invention is used as raw material to prepare ABS resin, and the preparation method is as follows:
[0083] (1) Coagulation / drying: 100 parts of ABS grafted latex emulsion was added to a reactor, heated to 95° C., 1.2 parts of H 2 SO 4 and 40 parts of deionized water were gradually added thereto, and the mixture was stirred evenly for 1 hour. The obtained coagulated emulsion was filtered with a 200-mesh stainless steel filter cloth to obtain a wet grafted powder, which was dried in a vacuum drum dryer at 60° C. and 2 KPaA for 4 hours to obtain a grafted powder with a moisture content of <1 wt %;
[0084] (2) Blending: Using a twin-screw extruder at 210° C., take XT500 as the MSAN resin for blending, and blend in a mass ratio of XT500: the above-mentioned grafted powder = 75:25. After cooling and granulation, a transparent ABS resin is obtained.
[0085] The impact strength, light transmittance and haze of each ABS were tested, and the test results are shown in Table 1.
[0086] Table 1. Performance test results
[0087]
[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. An ABS graft latex, characterized in that: Including polybutadiene latex, comonomer, emulsifier, initiator; The comonomers include styrene monomers, acrylonitrile monomers and methacrylate monomers.
2. The ABS grafted latex according to claim 1, characterized in that The amount of the comonomer is 50-200% of the dry weight of the polybutadiene latex; Preferably, the emulsifier is used in an amount of 0.5-5% of the dry weight of the polybutadiene latex; Preferably, the total amount of the initiator is 0.1-1% of the dry weight of the polybutadiene latex.
3. The ABS grafted latex according to claim 1, characterized in that: The styrene monomer is selected from one or more of styrene, α-methylstyrene, p-methylstyrene and vinyltoluene; The acrylonitrile monomer is one or more selected from acrylonitrile, methacrylonitrile and ethacrylonitrile; The methacrylate monomer is selected from one or more of methyl methacrylate, ethyl methacrylate, propyl methacrylate, and 2-ethylhexyl methacrylate.
4. The ABS graft latex according to any one of claims 1 to 3, characterized in that: The emulsifier is selected from carboxylates with 10 to 20 carbon atoms, preferably one or more of potassium oleate and fatty soap, and the mass proportion of carboxylates with less than 17 carbon atoms in the emulsifier is greater than 20%; Preferably, the initiator is a peroxide, preferably one or more of dicumyl peroxide, cumyl hydroperoxide, and tert-butyl hydroperoxide.
5. The ABS graft latex according to any one of claims 1 to 4, characterized in that: The total weight of the comonomer is 100%, and the raw materials are included in the following weight ratios: 10-30wt% styrene monomer, 5-20wt% acrylonitrile monomer, 60-80wt% methacrylate monomer; Preferably, the particle size of the polybutadiene latex is 260-350 nm, and the solid content is 40-60 wt %.
6. The ABS graft latex according to any one of claims 1 to 5, characterized in that: A chain transfer agent, a complexing agent, a reducing agent, a co-reducing agent or water is also added to the polymerization reaction; Preferably, the chain transfer agent is one or more of n-octyl mercaptan, tert-dodecyl mercaptan, and n-dodecyl mercaptan, preferably tert-dodecyl mercaptan; Preferably, the complexing agent is one or more of trisodium nitrilotriacetate, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium pyrophosphate, sodium hexametaphosphate, preferably sodium pyrophosphate; preferably, the auxiliary reducing agent is one or more of sodium dithionite, sodium formaldehyde sulfoxylate, isoascorbic acid, glucose, lactose, preferably glucose; preferably, the reducing agent is one or more of ferrous sulfate, ferrous chloride, sodium bisulfite, preferably ferrous sulfate; Preferably, the amount of the chain transfer agent is 0.1-1% of the dry weight of the polybutadiene latex; Preferably, the complexing agent is used in an amount of 0.1-1% of the dry weight of the polybutadiene latex; Preferably, the reducing agent is used in an amount of 0.001-0.01% of the dry weight of the polybutadiene latex; Preferably, the amount of the reducing agent is 0.1-1% of the dry weight of the polybutadiene latex; Preferably, the amount of water used is 50-100% of the dry weight of the polybutadiene latex.
7. A method for preparing the ABS graft latex according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing polybutadiene latex, comonomer, emulsifier and initiator to react and polymerize to obtain ABS grafted latex; Preferably, the comonomer can be added in batches or continuously by dropwise addition.
8. The preparation method according to claim 7, comprising the following steps: 1) Base stage: Add polybutadiene latex, part of the comonomer, part of the initiator, emulsifier and water into the reactor, stir and swell first and then heat to polymerize; 2) Continuous dropping stage: the remaining comonomer and initiator are added dropwise to the reactor, and the reaction is continued to be complete to obtain ABS grafted latex; Preferably, in step 1), the polymerization reaction temperature is 40-80°C, preferably 50-70°C; Preferably, the amount of the comonomer added in step 1) is 10-50% of the total mass of the comonomer; Preferably, the amount of the initiator added in step 1) is 10-50% of the total mass of the initiator; Preferably, in step 2), the polymerization reaction temperature is 40-90°C, preferably 50-80°C; Preferably, the dropwise addition time of the comonomer and the initiator in step 2) is 1-5 hours.
9. Use of the ABS graft latex according to any one of claims 1 to 6 or the ABS graft latex prepared by the preparation method according to claim 7 or 8 in preparing transparent ABS resin.
10. A method for preparing a transparent ABS resin, characterized in that: The following steps are involved: The ABS grafted latex prepared by the method is coagulated and demulsified to obtain ABS rubber powder, and then mixed and extruded with MSAN resin through an extruder to obtain transparent ABS resin; Preferably, MSAN resin refers to a methyl methacrylate-styrene-acrylonitrile copolymer having a refractive index of 1.515±0.005, and preferably has a weight average molecular weight of 100,000-140,000; Preferably, the mass ratio of the ABS rubber powder to the MSAN resin is (20-30):(70-80).
Citation Information
Patent Citations
Thermoplastic resin having uniform composition and narrow molecular weight distribution, and method for preparing the same
CN101336255A
A transparent ABS resin composition with excellent impact resistance, scratch resistance, and transparency.
CN104136530B
Method for preparing diene-based rubber polymer, diene-based rubber polymer prepared thereby, core-shell structured acrylonitrile-butadiene-styrene graft copolymer comprising same
CN107001515A
Method for production of graft copolymerized latex
CN1148603A
Preparation method and application of ABS (Acrylonitrile Butadiene Styrene) grafted latex
CN117567693A
Cited By
Modified ABS (Acrylonitrile Butadiene Styrene) resin and preparation method and application thereof
CN120737509A
ABS (Acrylonitrile Butadiene Styrene) rubber powder, low-haze transparent ABS resin and preparation method thereof
CN121203083A